Corporate Social Responsibility (CSR) Berbasis Shariah Enterprise Theory (SET) Dalam Meningkatkan Kepercayaan Masyarakat - Sudirman Sudi (Universitas Darussalam Gontor, 2021)
The purpose of this study is to describe Corporate Social Responsibility (CSR) based on Shariah Enterprise Theory (SET) and the impact of analyzing it in increasing public trust by internalizing elements of faith and trust. Absolute ownership is in the hands of Allah Almighty, humans are only given the mandate for the available resources, because human nature is as khalifatullah fil ardh (Allah's representative on earth). Because at this time, there are still many businesses that only have a profit oriented orientation solely with the aim of prioritizing parties related to the company, but forgetting the impact and consequences of the company's activities. The current phenomenon is that the implementation of CSR Employment activities is carried out only as a fulfillment of obligations. The results show that CSR based on SET is not only a solution to social conflicts, but is able to give the community trust in the company, then a positive image will be able to be increased and have a value of sustainability or sustainability.Keywords: CSR, SET, Social Conflict, Trust